Mapping The Evolution of The Literature on Competence and Vocational Education Readiness In The Global Value Chain: A Bibliometric Analysis - Fuad Abdillah (Jurnal Teknologi Pendidikan, 2025)
Globalization and digital transformation have changed the structure of the global value chain, demanding vocational education to produce graduates with adaptive competencies facing the complexities of Industry 4.0 and sustainability principles. The inequality between the acceleration of technological change and the ability of institutions to update the curriculum creates an urgency for the systematic mapping of knowledge fragmentation in the academic literature. This study maps the evolution of the global literature on the competence and readiness of vocational education to face global value chain challenges. Data was obtained from the Dimensions AI platform for the period 2000–2025 with a focus on English-language documents related to vocational education and SDG 4. Bibliometric analysis using VOSviewer 1.6.18 maps the country-institution collaboration network, thematic trends through keyword co-ocurence, as well as publication density and timeline visualization with a minimum parameter of three keyword occurrences and two institution-state entity collaborations. The results identified three dominant thematic clusters: continuing education, digital transformation, and link-and-match policies, with the dominance of publications from the United States (830) and the United Kingdom (620) and a significant increase of 33.9% by 2025. The research reveals geographical biases in knowledge production and the shift in research focus from conventional curricular aspects towards the integration of digital competencies and sustainability in response to global value chain dynamics. The findings provide an evidence-based intellectual map to identify critical research gaps and design vocational education policies that are inclusive and responsive to the demands of a sustainable global economy.